2003
DOI: 10.1073/pnas.1735481100
|View full text |Cite
|
Sign up to set email alerts
|

Extensive repetitive DNA facilitates prokaryotic genome plasticity

Abstract: Prokaryotic genomes are substantially diverse, even when from closely related species, with the resulting phenotypic diversity representing a repertoire of adaptations to specific constraints. Within the microbial population, genome content may not be fixed, as changing selective forces favor particular phenotypes; however, organisms well adapted to particular niches may have evolved mechanisms to facilitate such plasticity. The highly diverse Helicobacter pylori is a model for studying genome plasticity in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
128
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 118 publications
(137 citation statements)
references
References 43 publications
(56 reference statements)
7
128
0
Order By: Relevance
“…The results indicated that the intra-genomic recombination of 100 bp-long direct repeat sequences in H. pylori is partially dependent on RecR and RecA, yet a large portion of the recombination event is RecA-independent. This is basically in agreement (with small variance) with the results of Aras et al [35] who reported that the repeat sequences of 100 bp or shorter recombined through a RecA-independent pathway. For the deletion cassette containing repeat sequences of 350 bp in length, inactivation of recR or recA resulted in a significant 4-fold or 35-fold decrease respectively in deletion frequency, indicating that RecR plays a significant role in recombination of IDS350, while this recombination was highly dependent on RecA.…”
Section: H Pylori Recro Pathwaysupporting
confidence: 93%
“…The results indicated that the intra-genomic recombination of 100 bp-long direct repeat sequences in H. pylori is partially dependent on RecR and RecA, yet a large portion of the recombination event is RecA-independent. This is basically in agreement (with small variance) with the results of Aras et al [35] who reported that the repeat sequences of 100 bp or shorter recombined through a RecA-independent pathway. For the deletion cassette containing repeat sequences of 350 bp in length, inactivation of recR or recA resulted in a significant 4-fold or 35-fold decrease respectively in deletion frequency, indicating that RecR plays a significant role in recombination of IDS350, while this recombination was highly dependent on RecA.…”
Section: H Pylori Recro Pathwaysupporting
confidence: 93%
“…As a consequence, the rate with which these errors occur varies in a locus-specific manner and is several orders of magnitude higher than point mutations in nonrepeat DNA regions (18). Bacterial repeats in protein coding or upstream of regulatory regions are responsible for phenotypic switches as well as cell adaptations to specific environmental challenges (3,32). Here, most SSRs were located in housekeeping genes, noncoding regions, and hypothetical proteins (14,31).…”
Section: Discussionmentioning
confidence: 99%
“…This view is supported by reports of rapid loss of clonality during infection, the high rates of mutation and recombination observed in H. pylori, and the bacterium's natural competence (13)(14)(15). In a pioneering study, Israel et al (13) examined the evolution of H. pylori in the setting of acid-peptic disease.…”
Section: N the United States And Canada As Well As In Northern Andmentioning
confidence: 99%